The Handbook of textile culture - Jefferies, Janis; Conroy, Diana Wood; Clark, Hazel (Bloomsbury, 2016)
In recent years, the study of textiles and culture has become a dynamic field of scholarship, reflecting new global, material and technological possibilities. This is the first handbook of specially commissioned essays to provide a guide to the major strands of critical work around textiles past and present and to draw upon the work of artists and designers as well as researchers in textiles studies. The handbook offers an authoritative and wide-ranging guide to the topics, issues, and questions that are central to the study of textiles today: it examines how material practices reflect cross-cultural influences; it explores textiles relationships to history, memory, place, and social and technological change; and considers their influence on fashion and design, sustainable production, craft, architecture, curation and contemporary textile art practice. This illustrated volume will be essential reading for students and scholars involved in research on textiles and related subjects such as dress, costume and fashion, feminism and gender, art and design, and cultural history.